MON-LB309 Prevalence and Characteristics of Patients With Primary Severe Hypercholesterolemia in a Multidisciplinary Healthcare System in the Midwest - Eid, Wael Emad (J Endocr Soc, 2020)
Background Severe hypercholesterolemia (SH) phenotype includes all subjects with LDL-c of 190 mg/dL or more regardless of cause. Those with SH have up to 5-fold long-term risk for coronary artery disease (CAD). Objectives To assess prevalence, characteristics & different aspects of clinical care for patients with primary SH in a multidisciplinary healthcare system in the Midwest. Subjects & methods A retrospective, record-based, cross-sectional study was conducted using datasets from unique electronic health records of living patients presenting at a U.S. metropolitan healthcare system from 01/01/2013 until 08/31/2019. Cases were identified as SH if maximum LDL-c during the timeframe was 190 mg/dL or more. Subjects not meeting this criterion were used as controls. Comorbidities considered included CAD, congestive heart failure (CHF), diabetes mellitus (DM), hypertension (HTN), obesity & smoking. Lipid lowering therapies including statin, ezetimibe, & PCSK9I use were also assessed. Statistical analyses, including t-tests & logistic regression, were conducted to identify differences between cases & controls. Results After exclusion of subjects with secondary dyslipidemia, 224,920 records were used for analysis. Of these, 3.0% (6755) had SH. Those with SH were older by an average of about 3.5 years as compared to the control group. The most populous age-gender subgroup was females aged 40-75 years (35.2%). In the absence of any of the 5 comorbidities (CAD, CHF, DM, HTN, obesity), patients with SH were more likely to have established care with primary care (95% CI = 65%-69%) compared to control (95% CI= 56.5% - 57.2%). Patients with SH had more comorbidities with overall comorbidity represented by their higher Hierarchical Condition Category (HCC) score (P=0.001). HTN (P=0.000), premature CAD (P=0.000) & obesity (P=0.017) were all slightly more prevalent in cases than control. Mean arterial BP, systolic BP, diastolic BP & lipid parameters (LDL-c, total cholesterol, HDL, TG & Lipoprotein(a)) were higher in patients with SH (P= 0.000) compared to control. Patients with SH were treated more with statins or ezetimibe compared to control (P=0.000). However, of SH subjects, only 61% were found to have been treated with statin & only 26% were treated with high intensity statin. In the absence of any of the 5 comorbidities, these are lower (52% & 16% respectively) for statin use & 3.5% for the use of Ezetimibe. Persistent elevation of LDL-c to 190 mg/dL or more was present in 31% (2102) of SH cases. Conclusion Prevalence of primary SH is 3% in our population. Patients with SH exhibit greater likelihood for comorbidities, including those related to CVD. Most patients with SH are seen in the primary care setting rather than by endocrinology or cardiology. The use of statins (generally), high intensity statins, and ezetimibe in those with SH is more than control but still below that recommended by guidelines.